2008
DOI: 10.1515/cclm.2008.183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypothyroidism, hyperthyroidism, and their treatment on parameters of oxidative stress and antioxidant status

Abstract: Our results reveal an increased generation of reactive oxygen species and impairment of the antioxidant system in patients with hyperthyroidism, and particularly in patients with hypothyroidism. These findings indicate that thyroid hormones have a strong impact on oxidative stress and the antioxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 43 publications
9
108
0
3
Order By: Relevance
“…The increase of SOD has been shown in the blood of patients with hyperthyroidism [6]. On the contrary, Erdamar et al [187] found decreased SOD activity in the blood samples of patients with hyperthyroidism.…”
Section: Antioxidant Statusmentioning
confidence: 97%
See 1 more Smart Citation
“…The increase of SOD has been shown in the blood of patients with hyperthyroidism [6]. On the contrary, Erdamar et al [187] found decreased SOD activity in the blood samples of patients with hyperthyroidism.…”
Section: Antioxidant Statusmentioning
confidence: 97%
“…This could be explained by the relative doses of vitamin E administered, as compared with the study of Sarandol [229] which were not enough to suppress the oxidative stress in hypothyroid rats. For the first time in the literature, Erdamar et al [187] showed that the level of vitamin E was significantly increased in patients with hypothyroidism, which might be due to an adaptation against oxidative stress provoked by hypothyroidism.…”
Section: Antioxidant Statusmentioning
confidence: 99%
“…[9][10][11][12][13] Recently, there is growing evidence that a change of reactive oxygen species (ROS) metabolism has been implicated in the aetiopathogenesis of several autoimmune disorders including Graves' disease and GO. [14][15][16] Bednarek et al 17,18 reported that the ROS and antioxidant enzymes were increased in peripheral blood of hyperthyroid patients and euthyroid patients with infiltrative ophthalmopathy. Lu et al 19 detected signals of oxygen free radicals in GO retroocular fibroblasts by using electron paramagnetic resonance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, no association between MDA elevation and hypothyroidism has been observed in sheep. Erdamar et al 21 demonstrated MDA elevation and lipid peroxidation in overt hypothyroidism and hyperthyroidism and concluded that thyroid hormones play an important role in oxidative stress. Moreover, CanoEuropa 22 reported a correlation between thyroid dysfunction and the induction of selective oxidative stress in the rat amygdala and hippocampus.…”
Section: Discussionmentioning
confidence: 99%